2020
DOI: 10.7554/elife.58487
|View full text |Cite
|
Sign up to set email alerts
|

A stepped-wedge randomised trial on the impact of early ART initiation on HIV-patients’ economic outcomes in Eswatini

Abstract: Background: Since 2015, the World Health Organisation (WHO) recommends immediate initiation of antiretroviral therapy (ART) for all HIV-positive patients. Epidemiological evidence points to important health benefits of immediate ART initiation; however, the policy's economic impact remains unknown. Methods: We conducted a stepped-wedge cluster-randomised controlled trial in Eswatini to determine the causal impact of immediate ART initiation on patients' economic welfare. Fourteen healthcare facilities were non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…While this paper focused on the effect of EAAA on patients’ health expenditures, universal test-and-treat programs may have substantial welfare benefits in addition to reducing health expenditures. As reported in separate manuscripts [ 42 , 43 ] we did not find that the EAAA intervention improved patient satisfaction nor increased patients’ productivity levels, employment, and living standards. These null effects, however, may be explained by a relatively short follow-up period.…”
Section: Discussionsupporting
confidence: 44%
“…While this paper focused on the effect of EAAA on patients’ health expenditures, universal test-and-treat programs may have substantial welfare benefits in addition to reducing health expenditures. As reported in separate manuscripts [ 42 , 43 ] we did not find that the EAAA intervention improved patient satisfaction nor increased patients’ productivity levels, employment, and living standards. These null effects, however, may be explained by a relatively short follow-up period.…”
Section: Discussionsupporting
confidence: 44%
“…These findings are in slight contrast to a stepped-wedge trial in Eswatini which found that immediate initiation of ART reduced health-care expenditures but had no shortterm improvement on employment. 32,33 Overall, our results suggest that the considerable investments needed to expand access to ART might have significant shortterm and long-term economic returns.…”
Section: Discussionmentioning
confidence: 75%
“…Our study builds upon the existing literature that has shown large and significant increases in employment and income following ART initiation. [8][9][10]17,18,32,33 However, with the exception of one study that evaluated economic outcomes of people living with HIV and their household members, relatively few of these studies have used a cluster-randomised trial design to evaluate the effects of early ART initiation on socioeconomic outcomes. Our results support the hypothesis that earlier ART initiation can protect employment and other economic indicators for adults and lead to benefits in children's education.…”
Section: Discussionmentioning
confidence: 99%
“…The final sample size was determined by pragmatic aspects such as the availability of a research assistant on a scheduled study day and the travel time to a clinic. Tablet-assisted personal interviews were conducted based on a self-developed questionnaire with new, adapted, and previously used questions [ 30 , 31 ] (Supplement A). The interview included questions about different categories of OOPE, the arrival time at the clinic, travel time to the clinic, forgone earning opportunities, and lost income.…”
Section: Methodsmentioning
confidence: 99%